2015
DOI: 10.1186/s12863-015-0293-x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the biological processes shaping the genetic structure of the Italian population

Abstract: BackgroundThe genetic structure of human populations is the outcome of the combined action of different processes such as demographic dynamics and natural selection. Several efforts toward the characterization of population genetic architectures and the identification of adaptation signatures were recently made. In this study, we provide a genome-wide depiction of the Italian population structure and the analysis of the major determinants of the current existing genetic variation.ResultsWe defined and characte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
10
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 66 publications
1
10
0
Order By: Relevance
“…To deepen the resolution of our analysis, we restricted the comparison between centenarians and the overall Italian population to a micro-geographical scale. Principal Component Analysis (PCA) showed that centenarians fitted into the previously described patterns of clear differentiation between peninsular Italians and Sardinians described by PC1, as well as of the latitudinal cline of variation pointed out by PC2 [ 13 , 31 ]. However, they seemed to be more homogeneous ( i.e.…”
Section: Resultsmentioning
confidence: 76%
“…To deepen the resolution of our analysis, we restricted the comparison between centenarians and the overall Italian population to a micro-geographical scale. Principal Component Analysis (PCA) showed that centenarians fitted into the previously described patterns of clear differentiation between peninsular Italians and Sardinians described by PC1, as well as of the latitudinal cline of variation pointed out by PC2 [ 13 , 31 ]. However, they seemed to be more homogeneous ( i.e.…”
Section: Resultsmentioning
confidence: 76%
“…Concerning the phylogeography of Italy, it is difficult to identify a clear genetic pattern able to discriminate southern, northern and central populations in spite of several attempts based on autosomal and uniparental markers [19][20][21][22][23][24] . Southern populations were mostly influenced by Greek and Arab colonizations, Northern Italians might reflect admixture with French and German-speaking populations, while Central Italy occupies its own intermediate position creating a continuous cline of variation across the peninsula (with Sardinians as outliers) 13,19,[25][26][27][28][29] .…”
mentioning
confidence: 99%
“…To date, several studies based on the analysis of classical and uniparentally-inherited markers provided evidence of appreciable Italian population structure, especially as concerns Y-chromosome lineages, while a more homogeneous mitochondrial DNA background was described 3 16 17 18 19 . Nevertheless, few autosomal genome-wide datasets have been generated until now to further disentangle this scenario and to explicitly test hypotheses related to occurrence of local adaptive events in diverse Italian subpopulations 20 21 22 . In fact, genome-wide data suggested the existence of potential genetic barriers between Italians and other Europeans 23 and further corroborated evidence for internal differentiation of the overall Italian population 14 22 24 .…”
mentioning
confidence: 99%